Stress and Coping Strategies Among Parents of Neonates Admitted in Neonatal Intensive Care Unit – a Hospital-Based Study - Maharjan, Ramu; Shrestha, Mangala; Pokharel, Nirmala; Rai, Gayatri; Karn, Basant; Chaudhary, Kriti; Adhikari, Bikram (Journal of Karnali Academy of Health Sciences, 2022)
Background: Parents can experience feelings of guiltiness, helplessness, distress, fear, and anxiety whose neonates areadmitted in Neonatal Intensive Care Unit (NICU) creating stressful family patterns and demanding coping mechanisms.This study aimed to assess stress and coping strategies among the parents of neonates admitted to NICU.Methods: A cross-sectional study was conducted among 60 parents of neonates admitted to NICU of BPKIHS, Dharan.Data was collected using Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) for stress score, and BriefCoping Orientation to Problems Experienced (COPE) Inventory for coping score through face-to-face interviews andentered and analyzed data in Statistical Packages for Social Sciences (version 16). Categorical variables were presentedas frequency and percentage whereas numeric variables as mean and standard deviation, paired t-test was used to comparemean stress and coping scores of parents. An independent sample t-test was used to compare mean stress score and copingstrategies with selected demographic variables.Results: Overall parental mean stress score was 3.14±0.48, higher among mothers compared to fathers (3.39±0.43;2.89±0.37; p-value